The Effect of Using Gum Arabic (Segalia Senegal) Creams on Whiting and Tightening the Skin as an Alternative to Chemical Cosmetics (International Journal of Environmental Sciences, 2025)
Gum arabic is a natural plant exudate of acacia trees. It is a complex polysaccharide with a branched structure and has excellent functional properties, such as high solubility and low viscosity. It is used in food products due to its emulsifying properties. Gum arabic is one of the best drying agents for plants and contributes to improving the quality and physical properties of powders like productivity, bulk density, and solubility. The results of physical examination in our investigation revealed that the gum Arabic had a specific weight of 1.0055, an Relative density of 1.0034 grams per centimeter, an PH level of 4.6 and a viscosity of 7.22 CPS. while the chemical examination for gum Arabic included Humidity at 25%, 30% was 6.70, 2.44 , while total sugars content at concentrations of 25% and 30% was 41.10, 39.12 /100gram dry weight. Finally total acidity values at concentrations of 25%, 30%, reaching 0.11% and 0.19%, respectively. Gum arabic contains natural chemicals, such as alkaloids and flavonoids, which accelerate the healing process of wounds and scars when applied topically. Gum arabic has a range of properties that tighten the face, improve skin texture, and smooth wrinkles, leaving the skin soft and supple. It also reduces puffiness under the eyes, as some cosmetic products, including anti-aging face creams, contain gum arabic.